Evaluation of the effect of increasing the organic load in the thermophilic co-fermentation of sugarcane industry by-products on hydrogen, ethanol and lactic acid generation - Ribeiro, Alexandre Rodrigues; Devens, Kauanna Uyara; Camargo, Franciele Pereira [UNESP]; Sakamoto, Isabel Kimiko; Varesche, Maria Bernadete Amâncio; Silva, Edson Luiz (Elsevier, 2024)
The effects of increased organic loading rate (OLR) on H2 production and soluble metabolites in a thermophilic anaerobic fluidized bed reactor (AFBR-AT) at 55 °C were evaluated by the fermentation of vinasse and molasses from sugarcane (at a ratio of 1:1). The OLR varied between 30 and 135 kg COD.m−3.d−1, while the hydraulic retention time (HRT) was fixed at 4 h, and the initial co-substrate concentration varied between 5 and 22.5 g COD.L−1. The thermophilic acidogenic reactor showed a maximum hydrogen yield (HY) (2.49 mmol H2.g−1CODapp) at an OLR of 30 kg COD.m−3.d−1 and a higher hydrogen production rate (HPR) (2.8 L H2.L−1.d−1) at an OLR of 45 kg COD.m−3.d−1. Increasing the OLR negatively influenced H2 production. The results showed an increase in ethanol (EtOH) concentrations of up to 47.3 times and lactic acid (HLa) concentrations of up to 15.2 times when comparing OLRs of 30 and 135 kg COD.m−3.d−1, indicating changes in metabolic pathways for acid formation at organic loads ≥90 kg COD.m−3.d−1. Thermoanaerobacterium was the bacteria with higher relative abundance and was directly involved in H2 production, while Lactobacillus was mainly involved in HLa production in higher OLR, decreasing H2 production instead. Besides that, higher OLRs were favorable for sulfidogenesis and the development of sulfate-reducing bacteria, such as Desulfobacterota, due to the higher COD/sulfate ratio in OLR 135 kg COD.m−3.d−1. According to the metabolic inference in this condition, the enzyme activity of sulfite reductase and sulfite dehydrogenase may have occurred, consuming H+, thereby reducing H2 production.
Keywords: Anaerobic fluidized bed reactor; Dark fermentation; Lactic acid bacteria; Metabolic prediction; Volatile organic acids; Wastewater reuse